Worldwide suicide mortality trends by firearm (1990-2019): A joinpoint regression analysis. - Irena Ilic; Ivana Zivanovic Macuzic; Sanja Kocic; Milena Ilic (PLoS ONE, 2022)
Introduction Suicide by firearm is a major public health problem in many countries. But, studies that investigated the mortality of suicide by firearm on a global scale are still limited. The aim of this study was to assess the global, regional and national trends in mortality of suicide by firearm from 1990 to 2019. Method Mortality data of suicide by firearm was presented using the age-standardized rates (ASRs, expressed per 100,000). Joinpoint regression analysis was used to assess trends of mortality of suicide by firearm: the average annual percent change (AAPC) with the corresponding 95% confidence interval (95%CI) was calculated. Results A total of 52,694 (45,110 male and 7584 female) deaths of suicide by firearm were reported worldwide in 2019. The global ASR of suicide by firearm was six-fold higher in males than in females (1.15 per 100,000 and 0.19 per 100,000, respectively), and varied greatly across countries: the highest rates were in Greenland (24.52 per 100,000 and 2.69 per 100,000, respectively) and the United States of America (10.13 per 100,000 and 1.66 per 100,000, respectively), while the lowest rates (0.05 per 100,000 or less) were observed in China, Japan and Singapore. Globally, the mortality of suicide by firearm had a decreasing tendency from 1990 to 2019 in both sexes together (AAPC = -2.0% per year; 95%CI = -2.1 to -1.9). Conclusion Decreasing trends in mortality of suicide by firearm were observed in majority of countries across the world, but not in all. Future research should determine more effective ways to further reduce mortality of suicide by firearm.